Pengembangan Media Pop Up Book Berbasis Permainan Pada Pembelajaran Tematik Di Sekolah Dasar - Febriani, Febriani; Andriana, Encep; Yuliana, Rina (UNIB Press, 2022)
This research aims to describe the stages of developing pop up book media, to determine the feasibility of pop up book media, and to determine student responses to pop up book media. The type of research used is R&D with research and development procedures from Borg and Gall which has been modified by Sukmadinata with development steps, namely; (1) Conducting preliminary studies, (2) Product planning, (3) Development of product drafts, (4) Individual trials (5) Revising the results of field trials, (6) Limited trials, (7) Completion of test products limited, (8) Extensive implementation test, (9) Final product improvement. The results of this study indicate that the material expert's assessment got an average score of 88% in the